The combined occluding effect of sodium fluoride varnish and Nd:YAG laser irradiation on dentinal tubules—A CLSM and SEM study. Issue 6 (8th April 2016) - Tosun, Samet; Culha, Emre; Aydin, Ugur; Ozsevik, Abdul Semih
Summary: The purpose of this study is to evaluate the dentinal tubule occlusion potential and penetration of Clinpro® White Varnish (5% sodium fluoride + tri‐calcium phosphate) in the presence or absence of Nd:YAG laser. Seventy‐five dentin samples collected from 38 freshly extracted human molars were randomly divided into five groups (n = 15). Groups A, B, D, and E were varnished with Clinpro, whereas group C (no treatment) served as the control group. Groups B and E were further irradiated with Nd:YAG laser (1.5 W, 10 Hz, 1 min). All study groups were subjected to pH cycling (kept in 0.3% citric acid 5 min/day for 5 days). Groups A, B, and C were evaluated for tubule occlusion using scanning electron microscopy. Groups D and E were evaluated for penetration with confocal laser scanning microscopy (SEM). Non‐parametric Kruskall–Wallis and Dunn's statistical tests were used for analysis of SEM results. The penetration depths were analyzed with one‐way ANOVA followed by Fisher's Least Significant Difference tests. Tubular occlusion of groups A and B were significantly greater than group C (p < 0.05). Tubular occlusion of group B were significantly greater than group A (p < 0.05). Penetration depth for group D was significantly greater than group E (p < 0.05). Laser application improved the tubular occlusion capacity of Clinpro. Contrary, laser reduced the penetration of Clinpro. SCANNING 38:619–624, 2016. © 2016 Wiley Periodicals, Inc.